David Wengrow, The Origins of Monsters: Image and Cognition in the First Age of Mechanical Reproduction. The Rostovtzeff Lectures. Princeton, Princeton University Press, 2020. xviii + 162 pp. ISBN 9780691202396 (paperback). USD 35.00 - Maydana, Sebastián Francisco (2020)
Fil: Maydana, Sebastián Francisco. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Departamento de Historia; Argentina